Exploring Teachers´ and Students´ Perceptions of Assessment Forms Used in Lecturing Case of Master One Students at the Department of English, Mohammed Cherif Messaadia University, Souk Ahras - Chaima BELOUCIF (My University, 2024)
ABSTRACT This study aims to investigate the perceptions of both students and teachers regarding the use of assessment forms in lecturing at the Department of the English Language at Mohamed Cherif Messaadia University in Souk-Ahras. It explores the effectiveness of assessment forms used in lecturing and examines whether teachers give importance to these forms. This exploratory, descriptive research utilized a qualitative and quantitative study to collect data through three instruments: non-participant observation, an in-depth semi-structured interview, and a student questionnaire. Non-participant observation was conducted in the second semester (2024) with a group of Master One English Language students over six sessions during the "Grammar Teaching" module, "Educational Psychology" and "Didactics of Literary" classes, with two sessions per module. Secondly, an in-depth semi-structured interview with five EFL teachers was conducted. Finally, a questionnaire was provided to Master One students. The results indicated that both teachers and students have a positive attitude toward the various assessment forms used in lectures. There is a strong alignment between teachers' and students' perceptions, highlighting the effectiveness of the current assessment methods and the significant role of feedback in enhancing the educational experience. --------------------- الملخص تهدف هذه الدراسة إلى التحقيق في تصورات كل من الطلاب والمعلمين بشأن استخدام استمارات التقييم في المحاضرات في قسم اللغة الإنجليزية بجامعة محمد الشريف مساعدية بسوق أهراس. تستكشف فعالية استمارات التقييم المستخدمة في المحاضرات وتفحص ما إذا كان المعلمون يولون أهمية لهذه الاستمارات. استخدمت هذه الدراسة التفسيرية الوصفية بحثًا نوعيًا و كميا لجمع البيانات من خلال ثلاث أدوات: الملاحظة غير المشاركة، المقابلة شبه المنظمة المعمقة، واستبيان الطلاب. تم إجراء الملاحظة غير المشاركة في الفصل الدراسي الثاني (2024) مع مجموعة من طلاب السنة الأولى ماستر في اللغة الإنجليزية على مدى ست جلسات خلال وحدات "تدريس القواعد"، "علم النفس التربوي" و"ديداكتيك الأدب"، بجلستين لكل وحدة. ثانياً، تم إجراء مقابلة شبه منظمة معمقة مع خمسة معلمي اللغة الإنجليزية كلغة أجنبية. أخيرًا، تم تقديم استبيان للطلاب السنة الأولى ماستر. أشارت النتائج إلى أن كل من المعلمين والطلاب لديهم موقف إيجابي تجاه استمارات التقييم المختلفة المستخدمة في المحاضرات. هناك توافق قوي بين تصورات المعلمين والطلاب، مما يبرز فعالية أساليب التقييم الحالية والدور الهام للتغذية الراجعة في تحسين التجربة التعليمية --------------------- Résumé Cette étude vise à examiner les perceptions des étudiants et des enseignants concernant l'utilisation des formulaires d'évaluation dans les cours au Département de langue anglaise de l'Université Mohamed Cherif Messaadia à Souk-Ahras. Elle explore l'efficacité des formulaires d'évaluation utilisés dans les cours et examine si les enseignants accordent de l'importance à ces formulaires. Cette recherche explicative et descriptive a utilisé une étude qualitative et quantitative pour collecter des données à travers trois instruments : l'observation non participante, une interview semi-structurée approfondie et un questionnaire destiné aux étudiants. L'observation non participante a été menée au deuxième semestre (2024) avec un groupe d'étudiants de Master 1 en langue anglaise sur six séances durant les modules de "L'enseignement de la grammaire", "Psychologie éducative" et "Didactique de la littérature", avec deux séances par module. Deuxièmement, une interview semi-structurée approfondie avec cinq enseignants d'anglais langue étrangère a été réalisée. Enfin, un questionnaire a été distribué aux étudiants de Master 1. Les résultats ont indiqué que les enseignants et les étudiants ont une attitude positive envers les différents formulaires d'évaluation utilisés dans les cours. Il existe une forte concordance entre les perceptions des enseignants et des étudiants, soulignant l'efficacité des méthodes d'évaluation actuelles et le rôle significatif des retours dans l'amélioration de l'expérience éducative.